A novel HLA allele, HLA‐DRB1*15:116, discovered in a Taiwanese unrelated hematopoietic stem cell donor. Issue 2 (10th June 2015) - Yang, K. L.; Hung, J. H.; Lin, P. Y.
<x xml:space="preserve">Abstract</x> One nucleotide substitution at residue 127 of HLA‐DRB1*15:01:01:01 results in a new allele, HLA‐DRB1*15:116.